Role of Sodium Butyrate Supplement on Reducing Hepatotoxicity Induced by Lead Acetate in Rats - Ahmed, Rusal M; Mohammed, Amira K (The Iraqi Journal of Veterinary Medicine, 2022)
Lead has always been a health risk in developing countries. Lead severely affects liver function. Butyrate is effective in treating inflammatory disorders in animals. Thus, this study aimed to determine whether sodium butyrate mitigates lead acetate-induced hepatotoxicity. In this research, 40 adult female albino rats were randomly assigned to one of four treatment groups for a duration of 35 days as follows: group 1 served as a control, group 2 received sodium butyrate (SB) orally at 200 mg/kg daily, group 3 received lead acetate (LA) orally at 50 mg/kg daily, and group 4 received both SB and LA (SB+LA) orally. Blood was collected for complete blood picture (CBC) and some serum biochemical evaluations. Liver samples were collected for histopathological examination. The rats that exposed to lead acetate showed a significant (P<0.05) elevation in globulin, total bilirubin, total serum protein, and total white blood cells with a decrease in total red blood cells, haemoglobin, and packed cell volume, while weight gain shows a significant (P<0.05) decrease in this group. Histologically showed pre-vascular infiltration of the nuclear cell. Body weight of Rat’s gavage with sodium butyrate showed a substantial (P<0.05) increase, as well as there, were improvements in red blood cells RBC, haemoglobin, and packed cell volume PCV with the normal histological structure of the liver and no pathological lesion in hepatocyte. The fourth group (SB+LA) showed a significant (P<0.05) decrease in total bilirubin, indirect bilirubin, and total white blood cells, while other tests in this group showed nearly the control group as a result of the effect of SB. In conclusion, sodium butyrate consumption effectively reduces the harmful effects of lead acetate and prevents liver damage.